Analisis Pengaruh Transformational Leadership Communication Dan Organization Identification Terhadap Organzational Trust Melalui Affective Organizational Commitment - Ragil Parikesit; Arwini Sumardi (Humantech : Jurnal Ilmiah Multidisiplin Indonesia, 2022)
This thesis explained about how the positive influence of Transformational Leadership Communication And Oganizational Identification to Organizational Trust Through Affective Organizational Commitment of bank employees in Indonesia. So that company goals wich had been targeted can be reach with the help of their employees. The impact shows that the Transformational Leadership Communication style and Organizational Identification that has run can create commitment inside the organization, also how trust impact can push the member of the organization to optimize their work to fulfill the company goal which emerge from the commitment. This study develops the internal condition of banks company in Indonesia, where the are 187 respondent become the sample of this study. There are four variables: Transformational Leadership Communication, Oganizational Identification, Organizational Trust, and Affective Organizational Commitment. The four variable are develop into 26 instrument. There are 7 hypotheses had been tested to produce a model of Transformational Leadership Communication for each sector. The research finding shows that 6 hypotheses are associated each other and proven to have positive significant effect. The resulting model also shows there was a variable that have indirect influence, which was Oganizational Identification. These findings can be use by companies, especially banks company to develop leader and employee preference on creating a reliable communications using trust and komitmen as motivation to reach goals company.